The Economic Efficiency of Green Technologies in the Context of Technologically Expandable Natural Resources and Finite Human Needs: A Post-Liberal Perspective - Mammadov, Mahabbat; Mammadova, Kamala; Aliyev, Ruslan (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026DO - 10.14505/tpref.v17.2(38).05, 2026)
This study examines the economic efficiency of green technologies within a post-liberal framework that challenges the classical assumption of finite natural resources and unlimited human needs. It conceptualizes natural resources as technologically expandable in effective terms, while empirically treating human needs as finite and subject to measurable saturation thresholds. Using a mixed-methods approach, the research integrates theoretical analysis with quantitative evaluation of secondary macro-level data from the IEA, FAO, World Bank, and UNDP. Key indicators include per-capita consumption thresholds, energy intensity, resource productivity, renewable energy potential, and circular economy adoption rates. Cross-national comparisons are employed to capture institutional and technological heterogeneity. The findings identify clear saturation points in energy, food, and water consumption, alongside continuous expansion of effective resource capacity driven by renewable energy technologies, efficiency gains, and circular economy practices. These results indicate that economic efficiency is maximized through need-oriented production and coordinated technological investment rather than demand-driven growth.